2023
DOI: 10.1177/20597002221142379
|View full text |Cite
|
Sign up to set email alerts
|

Providing a clearer insight into how sport-related concussion and physical pain impact mental health, cognition, and quality of life

Abstract: Sport-related concussion (SRC) and physical pain are both associated with poor mental health, impaired cognition, and reduced quality of life. Despite SRC and physical pain often co-occurring, there is little research that investigates these two factors together, and therefore it is difficult to conclude which of these contributes to the negative outcomes associated with them. Therefore, the present study aimed to investigate the effect of SRC and physical pain on mental health, cognitive ability, and quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Therefore, although the odds ratios at first present one aspect of the data, the confidence intervals provide a more holistic picture, and that is the message we want our readers to take. As well as the risk that SRC poses to mental health, the present study also supports prior research that indicates the danger of experiencing physical pain [6,62] which is common in sport and therefore justifying the development of a simple risk metric. From our analysis, we identified that participants were 1.38 times more likely to be depressed for every increasing score of physical pain reported using the NRS-11.…”
Section: Plos Onesupporting
confidence: 87%
See 3 more Smart Citations
“…Therefore, although the odds ratios at first present one aspect of the data, the confidence intervals provide a more holistic picture, and that is the message we want our readers to take. As well as the risk that SRC poses to mental health, the present study also supports prior research that indicates the danger of experiencing physical pain [6,62] which is common in sport and therefore justifying the development of a simple risk metric. From our analysis, we identified that participants were 1.38 times more likely to be depressed for every increasing score of physical pain reported using the NRS-11.…”
Section: Plos Onesupporting
confidence: 87%
“…This may be due to prevalence rates ranging from 21% in the USA [1] and 43% in the UK [2] in young adults that visibly exceed the 3.8% of the general population that suffer from the disorder [3]. Several risk factors are commonly reported, including biological sex [2,4], physical pain [5][6][7], and sport-related concussion [SRC; [8][9][10]. Despite these links, it is continuously reported that athletes will accept the risk of experiencing physical pain [11][12][13] and sustaining SRC [14] when competing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations